Características de sono e de qualidade de vida em crianças e adolescentes com doenças respiratórias obstrutivas crônicas - Lumertz, Magali Santos (2021)
Sleep is necessary for human survival, being essential for physical and mental health maintenance in children and adolescents. However, sleep deprivation and/or poor sleep quality has become something common in contemporary society, affecting even the pediatric population. Sleep disorders in childhood and adolescence are associated with several negative health consequences even for individuals with underlying conditions. On the other hand, it´s reasonable think that the pediatric population with chronic obstructive respiratory diseases could have a poor sleep secondary to its own respiratory disease symptoms. So, there is a bidirectional relationship between sleep and chronic obstructive pulmonary diseases in childhood, although there is a limited evidence for it. As instance, there is a restricted number of studies evaluating sleep quality and/or duration and its impact on these subjects’ quality of life. And this is more restricted in pediatric individuals with severe asthma (SA) and post infectious bronchiolitis obliterans (PIBO). Therefore, the goals of the current study were to describe sleep aspects and quality of life of pediatric patients with chronic obstructive respiratory diseases - as cystic fibrosis (CF), SA and PIBO - and to evaluate if there is a correlation between sleep quality and quality of life of these subjects. Forty-six individuals were included: 30 with CF, 09 with severe asthma and 07 with BOPI. Almost 2/3 of the children and adolescents’ parents scored at least 39 points in SDSC, suggesting they had poor sleep quality. Total higher medians were significantly observed in severe asthmatics individuals (76 points; p= 0.001 in comparison to others). Patients and their guardians scored a median of 77 and 80 points respectively in Peds-QL, being those responsible for CF individuals presented higher values than those in other groups (85 points versus 64 and 65; p 0.014). This finding seems to be independent on socioeconomic status, as there was no difference in have or not health insurance. There was inversely moderate correlation between sleep disorders and quality of life (r= -0.532 for kids answer and - 0.606 for parents respectively, with p< 0.001). Therefore, children and adolescents with chronic obstructive respiratory diseases have impairment in their sleep quality and quality of life. Besides, sleep and quality of life have a moderate correlation in these individuals.